Neurodevelopmental Outcome in Very Low Birth Weight Infants Exposed to Donor Milk - Patra, Kousiki; Greene, Michelle M.; Tobin, Grace; Casini, Gina; Esquerra-Zwiers, Anita L.; Meier, Paula P.; Patel, Aloka L. (American Journal of Perinatology, 2021)
Objective This study was aimed to evaluate the impact of donor milk (DM) received in the first 28 days of life (DOL) on neurodevelopmental (ND) outcome at 20-months corrected age (CA) in very low birth weight (VLBW) infants.Study Design A total of 84 infants born in 2011 to 2012 who received only mother's own milk (MOM) and/or preterm formula (PF) was compared with 69 infants born in 2013 to 2014 who received MOM and/or DM. Daily enteral intake of MOM, DM, and PF was collected through 28 DOL. ND outcomes were assessed with the Bayley-III. Multiple regression analyses adjusted for the effect of social and neonatal risk factors alongside era of birth on ND outcome.Results Infants exposed to DM were born to older mothers (p < 0.01) and had higher incidence of severe brain injury (p = 0.013). Although DM group infants received first feed at earlier DOL (p < 0.001), there were no differences in MOM intake at DOL 14 or 28 between the two groups. In regression analyses, DM group did not predict 20-month ND outcome.Conclusion There were no differences in ND outcome between infants born before and after the introduction of DM. This may have been due to the similar percent of MOM at DOL 14 and 28 in the two eras.Key Points
Keywords: donor milk; neurodevelopmental outcome; VLBW infant